Diverse plant mixtures sustain a greater arbuscular mycorrhizal fungi spore viability than monocultures after 12 years. (29th June 2020) - Dietrich, Peter; Roscher, Christiane; Clark, Adam Thomas; Eisenhauer, Nico; Schmid, Bernhard; Wagg, Cameron
Abstract: Aims: Intensive land management practices can compromise soil biodiversity, thus jeopardizing long-term soil productivity. Arbuscular mycorrhizal fungi (AMF) play a pivotal role in promoting soil productivity through obligate symbiotic associations with plants. However, it is not clear how properties of plant communities, especially species richness and composition influence the viability of AMF populations in soils. Methods: Here we test whether monocultures of eight plant species from different plant functional groups, or a diverse mixture of plant species, maintain more viable AMF propagules. To address this question, we extracted AMF spores from 12-year old plant monocultures and mixtures and paired single AMF spores with single plants in a factorial design crossing AMF spore origin with plant species identity. Important Findings: AMF spores from diverse plant mixtures were more successful at colonizing multiple plant species and plant individuals than AMF spores from plant monocultures. Furthermore, we found evidence that AMF spores originating from diverse mixtures more strongly increased biomass than AMF from monocultures in the legume Trifolium repens L. AMF viability and ability to interact with many plant species were greater when AMF spores originated from 12-year old mixtures than monocultures. Our results show for the first time that diverse plant communities can sustain AMF viability in soils and demonstrate the potential of diverse plant communities to maintain viable AMF propagules that are a key component to soil health and productivity.